Civil liability for emotional abandonment: an integrative review of the literature (Revista Científica Integrada, 2025)
Objective: To examine the civil liability of parents for emotional abandonment, considering impacts on personality rights and the development of Brazilian case law. Methods: Integrative qualitative review across national legal databases (SciELO, LILACS, CAPES, BDJur/STJ, and Google Scholar), including studies from 2010 to 2024 in Portuguese and English directly addressing civil liability for emotional abandonment. Selection followed PRISMA, yielding seven studies for analysis. Results: Emotional abandonment is identified as a violation of personality rights, supported by the principles of dignity, comprehensive protection, and responsible parenthood. STJ case law remains divided: earlier 4th Panel precedents denied compensation; since 2012, the 3rd Panel has admitted damages, generally requiring proof of harm and causation. Doctrine splits between those recognizing affection as a protected legal interest and those denying a legal duty to love. Conclusion: Civil liability for emotional abandonment has strong constitutional and doctrinal support but faces evidentiary challenges and non-uniform case law. Damages serve compensatory and pedagogical functions without restoring bonds. Normative gaps persist, and more objective criteria for harm assessment are needed.
Keywords: Emotional abandonment; Civil liability; Family law; Compensation; Moral damages